In sync through laughter? An fNIRS hyperscanning study on neural synchrony and social connection - Schäfer, Verena T.; Hoehl, Stefanie; Pletti, Carolina (Frontiers in Neuroscience, 2026)
Laughter is a widespread social behavior that has been associated with increases in social connection. However, the mechanisms behind this link are not yet well understood. We hypothesized that laughter supports positive social outcomes by enhancing neural synchrony during social interactions. Neural synchrony is a process of mutual alignment of brain areas, which has been shown to positively affect social interactions. In a 2 × 2 design, participant pairs watched either funny or neutral videos (Laughter Manipulation: yes/no), either together or separately (Social Context: yes/no). Afterwards, they engaged in a 10-minute free interaction. Laughter behavior was annotated during both phases. Neural synchrony was measured using fNIRS hyperscanning for both phases and quantified across frontal and temporal regions using Wavelet Transform Coherence. As social outcomes, we measured Liking, Prosociality, and Bonding after the free conversation. We tested our hypotheses with Bayesian models that assessed the effects of Laughter and Social context on social outcomes, with synchrony modeled as a mediator. Parameter estimates for the effects of Laughter and Social Context on interpersonal neural synchrony were close to zero, with Bayes Factors indicating evidence for the null hypothesis. Similarly, the effects of Laughter and Social Context on Liking, Prosociality, and Bonding showed no effects. However, model comparisons provided evidence for annotated Laughter Behavior as a predictor of Liking, Prosociality, and Bonding. Mediation analyses revealed no overall effect, but some findings stood out. We observed a negative association between right IFG and right TPJ synchrony during the manipulation phase and later Liking, and a positive association between right and left IFG synchrony and subsequent Prosociality. Additionally, synchrony during the free interaction phase between the left IFG and right TPJ predicted Liking and synchrony between the left and right TPJ predicted Bonding. In total, our findings show no direct link between Laughter and neural synchrony. However, Laughter Behavior was associated with social outcomes. Additionally, neural synchrony was also linked to social outcomes, with distinct positive and negative associations depending on the brain regions involved. These results highlight the complexity of the relationship between laughter, neural synchrony, and social connection, suggesting the need for further research.